Learning management emphasizing desirable characteristics of students in Buddhist university - Homsombat, Poolsak; Phisaiphun, Krerk; Jantharach, Nakorn; Ruangsan, Niraj; Sawaengwong, Phathomsit; Sriburin, Eakachai; Marasi, Sarinya (Linguistics and Culture Review, 2021)
This paper aims to study the learning management emphasizing desirable characteristics (LMDC) of students in Buddhist university in Thailand based on documentary research methodology. The finding reveals that LMDC in Buddhist University is carried out according to the qualifications-framework including 1) ethical and moral development, 2) knowledge, 3) cognitive skills, 4) interpersonal skills and responsibility, 5) numerical analysis skills, communication and information technology skills, and 6) learning management science methodology (added in teaching profession curriculum) by integrating with digital competency and 9 characteristics.